The Impact of Later Tracking on Mortality by Parental Income in Finland - Bastian Ravesteijn; Hans van Kippersluis; Mauricio Avendano; Pekka Martikainen; Hannu Vessari; Eddy van Doorslaer (Tinbergen Institute, 2017)
We investigate whether later educational tracking reduced the intergenerational persistence of socioeconomic disparities in mortality in Finland,where the tracking age was raised from 11 to 16 in the 1970s. We use a difference-in-differences approach that exploits the gradual rollout of the reform. We find that late tracking did reduce disparities in mortality around the age of 50 by parental income for men. However, the longevity gains of men from low-income families seem to have come at the cost of increased mortality among men who grew up in high-income families. This raises questions about the welfare implications of the reform.
Keywords: C21; I14; I24; 330; Education; mortality; tracking; Difference-in-Difference; Finland